An Inquiry Into the Patient Safety Management Patterns: A Review Study - Seyed Jalil Hosseinin Irani; Leila Riahi; Ali Komeili; Reza Masoudi (Shahrekord University of Medical Sciences, 2019)
Background and aims: Patient safety, as one of the main components of the health care quality, implies avoiding any injury and damage to the patient when providing health care services. In other words, patient safety means his or her safety against any adverse and harmful event when receiving health care services. Based on the above-mention explanations, the present study was conducted to determine the patterns of patient safety management. Methods: A systematic review method was used to meet the objectives of the study. In order to access the scientific documentation and evidence related to the subject published during 1998-2018, English keywords including "Patient Safety Model", "Patient Safety", and "Patient Safety of Management" were searched in Medine, PubMed, and Google Scholar databases and Persian versions of these keywords were also looked for in Jihad-e Daneshgahi's Scientific Information Database (SID) and Iranian Journals database (Magiran). Results: The findings of this study suggested that most of the studies on designing a model for patient safety highlighted important dimensions including guidance and leadership, communication, organizing, information management, control and monitoring, participation and decision-making, as well as planning and coordination. Conclusion: In general, using patterns and frameworks designed for patient safety improves patient safety against uncertain incidents since the human and financial consequences of such incidents impose overwhelming sufferings on patients.